(untitled) (Bangladesh Journal of Medical Science, 2021)
Objective: To compare the efficacy of Dynamic exercise and Closed kinematic exercise combined with stretching in adhesive capsulitis. Background of the study: Adhesive capsulitis is a condition characterized by stiffness and pain in the shoulder joint. It is a painful and disabling disorder of unclear cause in which the shoulder capsule, the connective tissue surrounding the shoulder becomes inflamed and stiff, restricting ROM and causing chronic pain. Methodology: This was an experimental study design with Pre-Post test. 30 samples were selected from 45 volunteers based on the inclusion criteria. Group A-Dynamic exercise with stretching, Group B-Closed kinematic exercise with stretching, SWD is commonly given to the patients for 1 week. Results: The result concludes both the groups showed improvement while group A received Dynamic exercise with stretching was comparatively better than the Group B received Closed kinematic exercise with stretching Bangladesh Journal of Medical Science Vol.20(2) 2021 p.368-373